2020
DOI: 10.3390/plants9111554
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition or Facilitation? Contrasted Inter-Specific Interactions in Sphagnum under Laboratory and Field Conditions

Abstract: In a natural environment, plants usually interact with their neighbors predominantly through resource competition, allelopathy, and facilitation. The occurrence of the positive effect of allelopathy between peat mosses (Sphagnum L.) is rare, but it has been observed in a field experiment. It is unclear whether the stability of the water table level in peat induces positive vs. negative effects of allelopathy and how that is related to phenolic allelochemical production in Sphagnum. Based on field experiment da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…There are some reports of facilitative effects of bryophytes on vascular plants (e.g., Lett et al , 2018 ; Soudzilovskaia et al , 2011 ). Reports that support chemical facilitation in bryophyte communities are few; we have only found two such studies, but they reported contradictory results between laboratory and field experiments and, thus, dependency on environmental conditions ( Liu et al , 2020a ; Liu et al , 2020b ) which suggests a need for further investigation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…There are some reports of facilitative effects of bryophytes on vascular plants (e.g., Lett et al , 2018 ; Soudzilovskaia et al , 2011 ). Reports that support chemical facilitation in bryophyte communities are few; we have only found two such studies, but they reported contradictory results between laboratory and field experiments and, thus, dependency on environmental conditions ( Liu et al , 2020a ; Liu et al , 2020b ) which suggests a need for further investigation.…”
Section: Discussionmentioning
confidence: 67%
“…Although most bryophyte studies concern exploitive competition, there is growing evidence that interference competition, in the form of chemical interference (allelopathy), occurs as well ( Liu et al , 2020a ). For example, growing protonema secretes morphogenetic substances, which regulate the development of other filaments and coordinate the growth and differentiation of neighbouring plants ( Reski, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms have not been extensively explored, there are many studies that show inhibitory activities of liverwort specialized metabolites against bryophyte spore germination or angiosperm seed germination and/or root growth ( Basile et al , 2003 ; Asakawa et al , 2013 a ; Wang et al , 2013 ; Whitehead et al , 2018 ; Liu et al , 2020 ). Allelopathy associated with these compounds could be an important factor for discouraging the establishment of vascular plants that would later shade bryophytes, and also for establishing balances of plant species and microbiomes within bryophyte communities.…”
Section: Specialized Metabolites and Stress Tolerance In Bryophytesmentioning
confidence: 99%
“…Studies have found extensive evidence of allelopathy influencing the structure of the bog microbial community ( Chiapusio et al , 2018 ; Hamard et al , 2019 ). There is also recent evidence for phenolics having an allelopathic function between plant species ( Liu et al , 2020 ), and for some volatile compounds enabling communication between Sphagnum species ( Vicherová et al , 2020 ).…”
Section: Specialized Metabolites and Stress Tolerance In Bryophytesmentioning
confidence: 99%
“…Future climate will be warmer, and the direct metabolic effects of higher temperatures on bryophytes and associated C and N cycles have been studied and reviewed elsewhere (Lindo et al ., 2013; He et al ., 2016; Ruklani et al ., 2021; Zhang et al ., 2023). Future precipitation levels will also vary in total amount, frequency, and intensity, and this will further impact bryophyte influences on the amount of water, C, and N being fixed, stored, or lost from ecosystems (Wang et al ., 2019; Liu et al ., 2020). However, our understanding of bryophyte‐mediated interconnected ecosystem processes of water, C, and N cycling is limited across ecosystems globally.…”
Section: Introductionmentioning
confidence: 99%